Management of Malaria in Pregnancy with Covid-19 - Ika Wijayanti; Desi (proceedinginternational, 2023)
Malaria is one of the most common diseases in the world. According to WHO in 2015 there were 214 million cases of malaria. In Indonesia, the percentage of positive cases of malaria in Papua Province in 2016 was 54.3%. The design of this research is descriptive with the type of descriptive research used is a case study. This study was conducted at the RSAL Dr. Soedibjo Sardadi Jayapura in August 2020 on a 37-year-old woman G3P2A0 who was 16 weeks pregnant at term, a single live intrauterine fetus with tropical malaria, reactive SARS CoV- 2igG antibodies. Malaria in pregnancy can cause pathological conditions both in pregnant women and in fetuses. In pregnant women, such as fever, hypoglycemia, anemia, acute pulmonary edema, kidney failure can even cause death. In the fetus it causes abortion, premature delivery, low birth weight, and fetal death. Prevention of malaria in pregnancy using mosquito nets, prophylaxis, mosquito repellent, and gauze for ventilation, and not having a habit of going outside at night or going out at night with a frequency of <2 times. Prevention efforts against COVID-19 are to break the chain of transmission by isolation, early detection, and basic protection such as maintaining cleanliness (hygiene), washing hands, and disinfecting. Chloroquine is still the drug of choice for the treatment of malaria in pregnancy and quinine for the treatment of severe malaria.